Legal Problems Aspects Of The Immunity And Its Impact On Criminal Responsibility According To Omani Legislation - Saud Muhammad Al-Azri; Abidah Abdul Ghafar (Al-Maarif University College (AUC) Iraq, 2024)
Volume 33 Isseu 4 Page (244-274)